Evaluation of mineral content of plants used in the management of sickle cell disease - Kitadi, Jules M.; Inkoto, Clément Liyongo; Kwilu, Joseph; Lengbiye, Emmanuel M.; Tshibangu, Damien S. T.; Tshilanda, Dorothée D.; Ngbolua, Jean-Paul Koto-Te-Nyiwa; Mbala, Blaise M.; Schmitz, Brigitte; Mpiana, Pius Tshimankinda (Orapuh Journal, 2024)
Introduction Sickle cell disease is a hereditary condition primarily identified in tropical areas. It is marked by significant anemia, vaso-occlusive seizures, and a heightened vulnerability to both viral and bacterial infections. Additionally, sickle cell disease is distinguished by the depletion of mineral elements during crises. Purpose The purpose of this investigation was to identify the mineral composition of ten plants, namely Alchornea cordifolia, Alternanthera bettzickiana, Annona senegalensis, Cyttaranthus congolensis, Dissotis brazzae, Justicia secunda, Harungana madagascariensis, Hura crepitans, Hypoxis angustifolia, and Vigna unguiculata, traditionally utilized by practitioners in the management of sickle cell disease. Methods In this study, the biological material consists of the leaves, bark, and seeds of ten plant species. These plants were collected in Kwilu, and the mineral composition was assessed through fluorescence spectrometric analysis. The detection and quantification of the mineral elements were done by X-ray fluorescence spectrometric method with an XEPOS fluorescence spectrometer. The analysis of the results was carried out through Excel. R Studio and SPSS software packages were used for the statistical analyses. Results The study identified a total of twenty-three mineral elements in each of these plants, including Potassium (K), Phosphorus (P), Calcium (Ca), Sodium (Na), Magnesium (Mg), Sulphur (S), Chlorine (Cl), as well as trace elements like Aluminum (Al), Silicon (Si), Vanadium (V), Chromium (Cr), Manganese (Mn), Iron (Fe), Nickel (Ni), Copper (Cu), Zinc (Zn), Selenium (Se), Bromine (Br), Molybdenum (Mo), Tin (Sn), Iodine (I), Barium (Ba), and Lead (Pb). Notably, Iron, Zinc, Selenium, Copper, Calcium, Magnesium, and Manganese were found to be mineral elements associated with sickle cell disease. Potassium and Calcium exhibited higher concentrations, while Lead, Tin, Bromine, Copper, and Nickel were present in trace amounts. Conclusion The results obtained confirm that these plants contain some mineral elements such as Fe, Zn, Mg, and Se that are useful for sickle-cell patients.